2024
DOI: 10.1038/s41598-024-56062-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of physio-mechanical, antioxidant and antimicrobial properties of starch–zinc oxide nanoparticles active films reinforced with Ferula gummosa Boiss essential oil

Hamid Sarhadi,
Fatemeh Shahdadi,
Ali Salehi Sardoei
et al.

Abstract: The production of surface compounds coated with active substances has gained significant attention in recent years. This study investigated the physical, mechanical, antioxidant, and antimicrobial properties of a composite made of starch and zinc oxide nanoparticles (ZnO NPs) containing various concentrations of Ferula gummosa essential oil (0.5%, 1%, and 1.5%). The addition of ZnO NPs improved the thickness, mechanical and microbial properties, and reduced the water vapor permeability of the starch active fil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…al. [38] confirmed that the addition of zinc oxide nanoparticles increased the thickness of the active layer, leading to an improvement in the antimicrobial properties of the films. As seen in Figure 3a,b, 24 h of accelerated UV aging did not affect the activity of the EZ coating against both strains.…”
Section: Antimicrobial Properties Analysismentioning
confidence: 56%
“…al. [38] confirmed that the addition of zinc oxide nanoparticles increased the thickness of the active layer, leading to an improvement in the antimicrobial properties of the films. As seen in Figure 3a,b, 24 h of accelerated UV aging did not affect the activity of the EZ coating against both strains.…”
Section: Antimicrobial Properties Analysismentioning
confidence: 56%